Application of Panel Method to Calculate Ship Resistance - Ngoc Tu, Tran; Manh Chien, Nguyen (International Journal of Engineering and Technology, 2018)
In this study, the ship resistance in calm water was calculated using panel method under potential flow theory. This is a CFD (Computational Fluid Dynamic) approach with the assumption that the fluid is non-viscosity. Therefore, only wave resistance is calculated by solving nonlinear free surface problems. The frictional resistance is predicted by ITTC formula. The calculation is performed with well-known benchmark case – Kriso Container ship (KCS) – where the experiment result of ship resistance is available to compare and validate the calculation.